2018
DOI: 10.5194/aab-61-293-2018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding with hemp and Camelina cakes on the fatty acid profile of duck muscles

Abstract: Abstract. Camelina (Camelina sativa L. Crantz) and hemp (Cannabis sativa L.) seed cakes are rich sources of n-3 polyunsaturated fatty acids (PUFAs). This study was carried out to investigate the effects of Camelina and hempseed cakes in the diet of ducks on the intramuscular fatty acid profile. Male ducks (n = 99) were randomly allocated to 3 dietary treatments: Control or C group (wheat-soybean-meal-barley-based diet with 15-20 % rapeseed cake), Experimental 1 or HEM group (with hempseed cake added at 15-20 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…Fatty acid profile of camelina cake and diets. Table 2 shows that the fatty acid profile of camelina cake used in our study and obtained by cold-pressing oil extraction method, is a rich source of α-linolenic acid (ALA, 29.47%), linoleic acid (LA, 21.09%), and oleic acid (17.69%).Similar results have been reported previously by Nain et al (2015) and Juodka et al (2018). The fatty acid composition of diets showed that the inclusion of 80 g/kg CAMC increased the ALA content (2.87-fold) and resulted in a 3.89-fold decrease of the LA: ALA ratio, compared with the classical diet.…”
Section: Resultssupporting
confidence: 88%
“…Fatty acid profile of camelina cake and diets. Table 2 shows that the fatty acid profile of camelina cake used in our study and obtained by cold-pressing oil extraction method, is a rich source of α-linolenic acid (ALA, 29.47%), linoleic acid (LA, 21.09%), and oleic acid (17.69%).Similar results have been reported previously by Nain et al (2015) and Juodka et al (2018). The fatty acid composition of diets showed that the inclusion of 80 g/kg CAMC increased the ALA content (2.87-fold) and resulted in a 3.89-fold decrease of the LA: ALA ratio, compared with the classical diet.…”
Section: Resultssupporting
confidence: 88%
“…(2015) . The Σ PUFA n-6 / n-3 ratios determined in the present study for all geese muscles were higher than those previous obtained for duck meat by Wołoszyn et al., 2006 , Juodka et al., 2018 , and Onk et al. (2018) (3.3–5.1, 3.3–3.39, and 5.0).…”
Section: Resultscontrasting
confidence: 88%
“…(2015) for native Turkish geese reared with 4 different fattening systems (37.3–40.7%). Similarly, the breast muscles from different breeds of ducks were characterized by a higher (31–42%) percentage of SFA ( Wołoszyn et al., 2006 , Juodka et al., 2018 ).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, it has been also observed that among, n-6 PUFAs, the hempseed products supplementation led to an enrichment of eggs and meat with the GLA [150,161], conferring to these food products a further unique features related to the biological anti-inflammatory and anti-proliferative properties of GLA that have important implications for human health. Similar GLA-enrichment was also shown in the muscle of ducks fed a 15-20% hempseed cake-supplemented diet [162].…”
Section: Hempseed Products As Livestock Supplementsupporting
confidence: 69%